USEFUL TOOLS TO PREDICT FUTURE PERFORMANCE? ANALYSIS OF FORMER INDIVIDUALLY PRIZED YOUNG SELECTED MALE BASKETBALL PLAYERS - Zsombor ZILINYI; Ágoston NAGY; Tamás STERBENZ; Botond Ágoston NAGY; Benedek Ágost NAGY (Cluj University Press, 2021)
Success in team sports foremostly depends on individual performance and the cooperation of the team members. We aimed to investigate the individual performance changes of youth awarded basketball players from youth to senior national team level. For this purpose we examined four game-related basketball statistics: Minutes Played (MP), Points Scored (PS), Rebounds (REB), and Assists (AST) both in youth and senior level with regression analysis. We collected all the individually prized players of former youth European Championships available on the most reliable websites (N=323). We used descriptive statistical methods and also investigated correlation between their prized performance and their senior peak performance on national level (p